Characterisation of the cytokine milieu associated with the up‐regulation of IL‐6 and suppressor of cytokine 3 in chronic hepatitis C treatment non‐responders. (14th February 2014) - Martinez, Danica; Palmer, Clovis; Simar, David; Cameron, Barbara A.; Nguyen, Nam; Aggarwal, Vipul; Lloyd, Andrew R.; Zekry, Amany
Abstract Background & Aims In chronic hepatitis C virus infection (CHC), expression of suppressor of cytokine signalling‐3 (SOCS3) has been shown to be associated with obesity and non‐response to antiviral therapy. In this study, we aimed to determine the effect of SOCS3 induction on the cytokine response in patients receiving Pegylated interferon (PegIFN) and ribavirin (RBV) therapy. Methods Peripheral blood mononuclear cells (PBMC) collected at baseline and at 12 weeks from CHC patients receiving PegIFN/RBV therapy were examined for mRNA and protein SOCS3 expression. Immunological assays were employed to examine cytokine production. Results There was increased expression of SOCS3 in PBMC of non‐responders at week 12 of therapy, when compared to treatment responders (P = 0.0001). The expression of SOCS3 correlated with body mass index (BMI) (r = 0.54; P = 0.01). Patients with low SOCS3 expression at week 12 of therapy had lower HCV‐specific IFN‐γ production in enzyme‐linked immunosorbent spot (ELISpot) assays (P = 0.01), and reduced ex‐vivo production of the anti‐HCV effector cytokines interleukin (IL)‐2 and tumour necrosis factor (TNF)‐α(P = 0.01 and P = 0.04 respectively). Analysis of serum cytokine levels revealed higher levels of IL‐6 at week 12 in the high SOCS3 expression group (P = 0.02) while IL‐6 levels correlated with SOCS3 expression in the entire cohort (P = 0.04). Ex‐vivo studies confirmed that IL‐6 induced SOCS3, and neutralisation of IL‐6 reduced levels of SOCS3. Conclusion In subjects with increased BMI and non‐response to antiviral therapy, the IL‐6/SOCS3 axis appears to play a crucial role in altering the anti‐HCV‐cytokine response associated with antiviral therapy.